Implementation of Problem Based Learning-Science Technology Engineering Art and Mathematics Module to Improve Students' Science Process Skills - Himatul Aliyah; Sulistyo Saputro; Sarwanto Sarwanto (Postgraduate, University of Mataram, 2025)
This study aims to analyze the improvement of students' science process skills after the implementation of PBL-STEAM-based science modules on simple mechines materials. This research development (R&D) uses a 4D approach from Thiagarajan, focused on the development stage. The instruments used include needs analysis questionnaires, SPS tests, expert validation sheets, and readability questionnaires. The data of this study was obtained from a validation questionnaire with an Aiken's V value filled out by media experts (0.893), material experts (0.897), linguists (0.881), and learning experts (0.887). The trial was limited to 15 students and 3 teachers showing a module readability of 90%. Field trials with pre-test and post-test resulted in an N-Gain value of 0.8, indicating a high increase in student SPS. Thus, PBL-STEAM-based science modules have proven to be feasible to improve students' science process skills.